Emission Spectral Control of a Silicon Light Emitting Diode Fabricated by Dressed-Photon-Phonon Assisted Annealing Using a Short Pulse Pair. (6th July 2014) - Kawazoe, Tadashi; Wada, Naoki; Ohtsu, Motoichi
Abstract : We fabricated a high-efficiency infrared light emitting diode (LED) via dressed-photon-phonon (DPP) assisted annealing of a p-n homojunctioned bulk Si crystal. The center wavelength in the electroluminescence (EL) spectrum of this LED was determined by the wavelength of a CW laser used in the DPP-assisted annealing. We have proposed a novel method of controlling the EL spectral shape by additionally using a pulsed light source in order to control the number of phonons for the DPP-assisted annealing. In this method, the Si crystal is irradiated with a pair of pulses having an arrival time difference between them. The number of coherent phonons created is increased (reduced) by tuning (detuning) this time difference. A Si-LED was subjected to DPP-assisted annealing using a 1.3 μ m (h ν = 0.94 eV) CW laser and a mode-locked pulsed laser with a pulse width of 17 fs. When the number of phonons was increased, the EL emission spectrum broadened toward the high-energy side by 200 meV or more. The broadening towards the low-energy side was reduced to 120 meV.